Investigating the Influence of Socio-Emotional Learning Intervention on Student Motivation and Academic Self-Efficacy in Indonesian Schools - Abid Nurhuda; Fiki Setiawan; Nadine Souheil Hasan Haidar (International Forum of Researchers and Lecturers, 2024)
This study investigates the impact of a Social and Emotional Learning (SEL) intervention on student motivation and academic self-efficacy in junior high schools in Indonesia. The research utilized a quasi-experimental design with pre-test and post-test assessments to measure changes in intrinsic motivation and academic self-efficacy among the participants. A total of 200 students were divided into an experimental group, which participated in the SEL program, and a control group, which did not receive the intervention. The SEL program, delivered over one semester, focused on improving students' emotional regulation, social skills, and self-awareness, with an emphasis on autonomy, competence, and relatedness. The results demonstrated significant improvements in both intrinsic motivation and academic self-efficacy for the experimental group, with average increases of +19.2 and +17.4 points, respectively. Statistical analysis showed that the SEL intervention had a significant positive effect, with t-values of 7.56 (motivation) and 6.32 (self-efficacy) and p-values less than 0.01. In contrast, the control group exhibited minimal changes in both variables. These findings suggest that SEL interventions can foster a more balanced approach to learning by enhancing both emotional and academic development. The study highlights the importance of incorporating SEL programs into the curriculum to support students' holistic growth and academic success.